Pengaruh School Burnout terhadap Perilaku Off-task pada Peserta Didik di SMP Negeri 1 Godean - Desi Litasari; Sri Hartini; Ulfa Danni Rosada; Hardi Prasetiawan (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This research is motivated by empirical findings at SMP Negeri 1 Godean, where high curriculum demands and academic expectations trigger symptoms of mental fatigue among students. Preliminary observations revealed that many students exhibited apathy and frequently engaged in non-academic activities during lessons, such as chatting or daydreaming, indicating issues with school burnout and off-task behavior. This study is crucial to empirically examine the extent to which burnout levels contribute to the frequency of student disengagement in the classroom. The research method employed is quantitative correlational with a simple linear regression design involving 200 students as samples selected through the stratified random sampling technique. Data were collected using a school burnout scale (Î± = 0.672) and an off-task behavior scale (Î± = 0.645), both of which have been tested for validity and reliability. Data analysis was performed using SPSS version 27 to test the hypothesis through the coefficient of determination (R2). The results indicate a significant influence of school burnout on off-task behavior, where an increase in academic burnout is directly proportional to the increased frequency of student withdrawal in the classroom. These findings highlight important implications for educational practice in schools, particularly in the development of preventive and intervention strategies aimed at strengthening students’ emotional regulation, academic engagement, and self-control to reduce school burnout and minimize off-task behavior.